Identification and validation of an anoikis-related lncRNA signature to predict prognosis and immune landscape in osteosarcoma - Zhang, Jun-Song; Pan, Run-Sang; Tian, Xiao-Bin (Frontiers in Oncology, 2023)
Background: Anoikis is a specialized form of programmed apoptosis that occurs in two model epithelial cell lines and plays an important role in tumors. However, the prognostic value of anoikis-related LncRNA (ARLncs) in osteosarcoma (OS) has not been reported. Methods: Based on GTEx and TARGET RNA sequencing data, we carried out a thorough bioinformatics analysis. The 27 anoikis-related genes were obtained from the gene set en-richment analysis (GSEA). Univariate Cox regression and least absolute shrinkage and se-lection operator (LASSO) analysis were successively used to screen for prognostic related ARLncs. To create the prognostic signature of ARLncs, we performed multivariate Cox re-gression analysis. We calculated the risk score based on the risk coefficient, dividing OS pa-tients into high- and low-risk subgroups. Additionally, the relationship between the OS im-mune microenvironment and risk prognostic models was investigated using function en-richment, including Gene ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), single-sample gene set enrichment analysis (ssGSEA), and GSEA analysis. Finally, the potential effective drugs in OS were found by immune checkpoint and drug sensitivity screening. Results: A prognostic signature consisting of 4 ARLncs (AC079612.1, MEF2C-AS1, SNHG6, and TBX2-AS1) was constructed. To assess the regulation patterns of anoikis-related LncRNA genes, we created a risk score model. According to a survival analysis, high-risk patients have a poor prognosis as they progress. By using immune functional analysis, the lower risk group demonstrated the opposite effects compared with the higher risk group. GO and KEGG analysis showed that the ARLncs pathways and immune-related pathways were enriched. Immune checkpoints and drug sensitivity analysis might be used to determine the better effects of the higher group. Conclusion: We identified a novel prognostic model based on four ARLncs signature that might serve as potential prognostic indicators that can be used to predict the prognosis of OS patients, and immunotherapy and drugs that may contribute to improving the overall survival of OS patients and advance our understanding of OS.